From Individualistic Capitalism to Philanthropic Capitalism (Sociología y tecnociencia, 2026)
This article aims to explain the understanding of capitalism and how philanthropic capitalism as a concept and implementation. It is clear that the concept of capitalism does not just sit in the economic definition, in the socio-political aspect capitalism is always placed in the position of the controlling social class, both clearly present and secretly. In principle, capitalism is always based on individual interests which are sometimes the most extreme. its egoistic. But there is a path of philanthropic capitalism that shows how capital can be a means of realizing humanity
Keywords: human, capital, philanthropic capitalism